Green Growth and Economic Performance - Walker,Seán; Karlsson,Tuva (2025)
In response to the emergency of climate change, green growth has emerged as an attractive pathway towards sustainable development. The environmental feasibility and economic consequences of green growth is a much debated topic among scholars. This thesis provides a panel data analysis of the relationship between green growth and economic performance in the industrial economies of Germany and Czechia between 2005 and 2019. This relationship is evaluated through three variables representing green growth, namely green Investment, green Innovation and green Trade. The main findings indicate that green Innovation has a slightly positive correlation to economic performance, while the relations of Investment and Trade to economic performance appear to be mixed. Consequently, the findings contribute to the complex debate on the relationship between green growth and economic performance and provide recommendations for policymakers and future research.
Keywords: Green Growth; Industrial Economies; Sustainable Development; Panel Data